Rapid increase in aggressive behavior precedes the decrease in brain aromatase activity during socially mediated sex change in Lythrypnus dalli - Black, Michael P. (2010)
In the bluebanded goby, Lythrypnus dalli, removal of the male from a social group results in a rapid behavioral response where one female becomes dominant and changes sex to male. In a previous study, within hours of male removal, aromatase activity in the brain (bAA) of dominant females was almost 50% lower than that of control females from a group in which the male had not been removed. For those females that displayed increased aggressive behavior after the male was removed, the larger the increase in aggressive behavior, the greater the reduction in bAA. To investigate whether decreased bAA leads to increased aggression, the present study used a more rapid time course of behavioral profiling and bAA assay, looking within minutes of male removal from the group. There were no significant differences in bAA between control females (large females from groups with the male still present), females that doubled their aggressive behavior by 10 or 20 minutes after male removal, or females that did not double their aggressive behavior within 30 minutes after male removal. Further, individual variation in bAA and aggressive behavior were not correlated in these fish. Whole brain decreases in aromatase activity thus appear to follow, rather than precede, rapid increases in aggressive behavior, which provides one potential mechanism underlying the rapid increase in androgens that follows aggressive interactions in many vertebrate species. For fish species that change sex from female to male, this increase in androgens could subsequently facilitate sex change.